Anion-polarisation-directed short-range-order in antiperovskite Li2FeSO - Coles, SW; Falkowski, V; Geddes, HS; Pérez, GE; Booth, SG; Squires, AG; O'Rourke, C; McColl, K; Goodwin, AL; Cussen, SA; Clarke, SJ; Islam, MS; et al. (Royal Society of Chemistry, 2023)
Short-range ordering in cation-disordered cathodes can have a significant effect on their electrochemical properties. Here, we characterise the cation short-range order in the antiperovskite cathode material Li2FeSO, using density functional theory, Monte Carlo simulations, and synchrotron X-ray pair-distribution-function data. We predict partial short-range cation-ordering, characterised by favourable OLi4Fe2 oxygen coordination with a preference for polar cis-OLi4Fe2 over non-polar trans-OLi4Fe2 configurations. This preference for polar cation configurations produces long-range disorder, in agreement with experimental data. The predicted short-range-order preference contrasts with that for a simple point-charge model, which instead predicts preferential trans-OLi4Fe2 oxygen coordination and corresponding long-range crystallographic order. The absence of long-range order in Li2FeSO can therefore be attributed to the relative stability of cis-OLi4Fe2 and other non-OLi4Fe2 oxygen-coordination motifs. We show that this effect is associated with the polarisation of oxide and sulfide anions in polar coordination environments, which stabilises these polar short-range cation orderings. We propose that similar anion-polarisation-directed short-range-ordering may be present in other heterocationic materials that contain cations with different formal charges. Our analysis illustrates the limitations of using simple point-charge models to predict the structure of cation-disordered materials, where other factors, such as anion polarisation, may play a critical role in directing both short- and long-range structural correlations.